THE INFLUENCE OF WORD WEBS GAME TOWARDS STUDENTS’ VOCABULARY MASTERY AT THE SECOND SEMESTER OF THE EIGHTH CLASS OF SMP DHARMAPALA BANDAR LAMPUNG - Presica, Nova Anggun; Febriyanti, Febriyanti (Lentera: Jurnal Ilmiah Kependidikan, 2014)
Vocabulary is entirely important to be learns. In order that the students can express their minds, make sentences, interact and also catch the meaning from the context. This research applied Word Webs Game in teaching vocabulary. This research analyzed the result of application of the technique in order to know the influence of Word Webs game.The number all population in this research are 161 students. It used an experimental method in this research. It took two classes as the sample. The sample is taken by using Cluster Random Sampling Technique. The form of the test is objective test that is multiple choice that consist of 50 items of vocabulary test.Before conducting the research, it is assumed that the students had the same characteristics, qualities and also status. The result of the research showed that there was positive influence of Word Webs Game towards students’ vocabulary mastery at the second semester at SMP Dharmapala Bandar Lampung in 2012/2013. It is shown from the distribution list df = 40 obtained the 3.24 and for α = 5 % or 2.00, α = 1 % or 0.01 = 2.66, so the result is 2.00 < 3.24 > 2.66. So, Ho is accepted and ha is rejected.The Average score of post test in experiment class was 68.75, while the average score of post test in control class was 57.67. It is indicated that the average score of post test in experiment class was higher than the average score of post test in control class. So, it can be concluded that there was positive influence in of Word Webs game towards students’ vocabulary mastery.